2019
DOI: 10.1039/c9cp03935j
|View full text |Cite
|
Sign up to set email alerts
|

Exploring chemical space with alchemical derivatives: alchemical transformations of H through Ar and their ions as a proof of concept

Abstract: Alchemical derivatives have been used previously to obtain information about transformations in which the number of electrons is unchanged. Here an approach for combining changes in both the number of electrons and the nuclear charge is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 68 publications
3
22
0
Order By: Relevance
“…Previous work using conceptual DFT in predicting atomic properties had also seen a dependence on transmutation direction. 33 This observed asymmetry in errors was also noted in work by others on diatomic molecules, which showed that the description of different target systems using the basis set of one reference system relied on the direction of ∆Z. 48 In the case for atoms, this appears to be due to the augmented finite basis sets for one element generally being slightly more suitable when describing anions than cations of another element.…”
Section: Alchemical Pessmentioning
confidence: 70%
See 1 more Smart Citation
“…Previous work using conceptual DFT in predicting atomic properties had also seen a dependence on transmutation direction. 33 This observed asymmetry in errors was also noted in work by others on diatomic molecules, which showed that the description of different target systems using the basis set of one reference system relied on the direction of ∆Z. 48 In the case for atoms, this appears to be due to the augmented finite basis sets for one element generally being slightly more suitable when describing anions than cations of another element.…”
Section: Alchemical Pessmentioning
confidence: 70%
“…To achieve a fundamental understanding of the general accuracy and transferability of these Taylor series approximations, we report the performance of quantum alchemy using Taylor series expansions in predicting electronic energies of single atoms and compare to experimentally observable quantities such as ionization energies, electron affinities, and spin multiplet gaps. Earlier work in this direction 33 , evaluating the alchemical derivatives in the context of conceptual DFT, focused on DFT methods. In this work, we study a correlated wavefunction method, namely the more accurate but more expensive CCSD(T) approach.…”
Section: Introductionmentioning
confidence: 99%
“…The left side of Equation ( 15) has been previously identified as an alchemical derivative. 39,43,[47][48][49][50][51][52][53][54][55][56][57][58][59] Alchemical derivatives are derivatives of the energy with respect to the atomic number of the atoms of a molecule. [46][47][48][49][50][51][52][53][54][55][56][57][58] Indeed, for a discrete distribution of nuclear charge, Equation ( 15) is the negative of derivative of the chemical potential with respect to the atomic numbers, also known as the alchemical (local) hardness, η alchem k , 53…”
Section: The Fukui Potential and Alchemical Derivativesmentioning
confidence: 99%
“…The left side of Equation () has been previously identified as an alchemical derivative 39,43,47–59 46–58 .…”
Section: The Fukui Potential and The Local Hardnessmentioning
confidence: 99%
See 1 more Smart Citation